A Library of Atomically Thin 2D Materials Featuring the Conductive‐Point Resistive Switching Phenomenon. Issue 7 (28th December 2020) - Ge, Ruijing; Wu, Xiaohan; Liang, Liangbo; Hus, Saban M.; Gu, Yuqian; Okogbue, Emmanuel; Chou, Harry; Shi, Jianping; Zhang, Yanfeng; Banerjee, Sanjay K.; Jung, Yeonwoong; Lee, Jack C.; et al.
Abstract: Non‐volatile resistive switching (NVRS) is a widely available effect in transitional metal oxides, colloquially known as memristors, and of broad interest for memory technology and neuromorphic computing. Until recently, NVRS was not known in other transitional metal dichalcogenides (TMDs), an important material class owing to their atomic thinness enabling the ultimate dimensional scaling. Here, various monolayer or few‐layer 2D materials are presented in the conventional vertical structure that exhibit NVRS, including TMDs (MX2, M = transitional metal, e.g., Mo, W, Re, Sn, or Pt; X = chalcogen, e.g., S, Se, or Te), TMD heterostructure (WS2 /MoS2 ), and an atomically thin insulator (h‐BN). These results indicate the universality of the phenomenon in 2D non‐conductive materials, and feature low switching voltage, large ON/OFF ratio, and forming‐free characteristic. A dissociation–diffusion–adsorption model is proposed, attributing the enhanced conductance to metal atoms/ions adsorption into intrinsic vacancies, a conductive‐point mechanism supported by first‐principle calculations and scanning tunneling microscopy characterizations. The results motivate further research in the understanding and applications of defects in 2D materials. Abstract : The library of atomically thin 2D materials featuring non‐volatile resistive switching can provide a promising and broad platform for exploring the sub‐nanometer scaling limit, which is beneficial for emerging device concepts. A dissociation–diffusion–adsorption (DDA) model is proposed to describe the common conductive‐point mechanism behind 2D‐materials‐based universal resistive switching and supported by systematic density functional theory (DFT) calculations showing favorable adsorption of metal into native defects.